2018
DOI: 10.1155/2018/9745601
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Roles of Inflammatory Markers in Pancreatic Cancer: Comparison between the Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio

Abstract: Background/Objectives This meta-analysis is aimed at investigating the prognostic roles of the inflammatory markers neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in patients with pancreatic cancer. Methods The correlations between high inflammatory marker expression levels and prognosis in 7105 patients with pancreatic cancer from 34 eligible studies were investigated. Additionally, subgroup analyses based on study location, tumor stage, treatment, and value cutoffs were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 58 publications
(41 reference statements)
0
41
1
1
Order By: Relevance
“…C-reactive protein) [1,19]. A meta-analysis of 34 studies including 7105 patients with pancreatic cancer revealed that high PLR and NLR were defined as values from 150 to 200, and 2 to 5, respectively [20]. They found a significant correlation between high PLR (HR=1.143, 95% CI: 1.037 to 1.259) and NLR (HR=1.737, 95% CI: 1.502 to 2.009) and poor survival.…”
Section: Funding: Nonementioning
confidence: 99%
See 1 more Smart Citation
“…C-reactive protein) [1,19]. A meta-analysis of 34 studies including 7105 patients with pancreatic cancer revealed that high PLR and NLR were defined as values from 150 to 200, and 2 to 5, respectively [20]. They found a significant correlation between high PLR (HR=1.143, 95% CI: 1.037 to 1.259) and NLR (HR=1.737, 95% CI: 1.502 to 2.009) and poor survival.…”
Section: Funding: Nonementioning
confidence: 99%
“…They found a significant correlation between high PLR (HR=1.143, 95% CI: 1.037 to 1.259) and NLR (HR=1.737, 95% CI: 1.502 to 2.009) and poor survival. Both parameters had no prognostic role in patients who underwent chemoradiotherapy [20]. Song et al conducted a meta-analysis of 8 studies including 1904 patients with pancreatic cancer [21], and found that the PLR was associated with decreased OS (HR=1.22, 95% CI: 1.04 to 1.43, P = 0.02), especially in Asian studies, patients with metastatic disease and for values of PLR over 150.…”
Section: Funding: Nonementioning
confidence: 99%
“…SIR markers such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple, easily available, and inexpensive to evaluate. Recent studies have shown that elevated NLR or PLR is associated with poor prognosis among patients with several types of cancers [678910].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and tumor growth are dependent factors, and increasing numbers of studies have elucidated the role of systemic inflammatory response mediators in various solid cancers [13,14]. Among them, GC is one of the popular foci of these investigations that evaluated cancerrelated inflammation and possible predictors in the preoperative period [6][7][8].…”
Section: Discussionmentioning
confidence: 99%